2010
DOI: 10.1590/s0034-737x2010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de ganho genético por diferentes critérios de seleção em genótipos de alfafa

Abstract: Estimates of genetic progress using different selection criteria in alfalfa genotypesThis study aimed to compare different selection criteria, indicate the selection method that provides larger estimates of genetic progress and identify superior genotypes for the evaluated morphological and bromatological characteristics. The experiment was conducted at Embrapa Pecuária Sudeste, São Carlos, São Paulo State, Brazil in a randomized blocks design, with two replicates. The evaluated characteristics were dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 9 publications
2
25
1
21
Order By: Relevance
“…The difference observed in the selection of genotypes by these two methodologies was also reported by Vasconcelos et al, (2010) when working with selection of progenies of alfalfa.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The difference observed in the selection of genotypes by these two methodologies was also reported by Vasconcelos et al, (2010) when working with selection of progenies of alfalfa.…”
Section: Resultssupporting
confidence: 53%
“…However, when the indices are compared in two phases, the genetic gains obtained by the two methodologies were similar; the Elston's index was superior for fruit number and rind thickness, while the index of Mulamba & Mock was superior for fruit mass and shell mass. Vasconcelos et al, (2010) found that the highest estimates of genetic gain for productive, morphological and chemical characteristics in superior genotypes of alfalfa were obtained with the indices of Mulamba & Mock (1978), distance from the ideotype and the Elston's index (1963). Cruz et al, (1993) and Costa et al, (2004) also found positive results using the indices of Mulamba & Mock in studies with corn and soybean, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the selection of superior progeny is no easy task, since characteristics of importance, the majority of which are quantitative, show complex behaviour, being influenced by the environment and interrelated in such a way that the selection or alteration of one causes a series of changes in another (RODRIGUES et al, 2013;SILVA et al, 2009;VASCONCELOS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another studies also report superiority of this index for alfalfa (VASCONCELOS et al, 2010), soybean (BÁRBARO et al, 2007), yellow passion fruit (ROSADO et al, 2012), popcorn (AMARAL JÚNIOR et al, 2010), cowpea (BERTINI et al, 2010), maize (RODRIGUES et al, 2011) and banana (LESSA et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…These indexes are widely used in several crops (BÁRBARO et al, 2007;AMARAL JÚNIOR et al, 2010;BERTINI et al, 2010;VASCONCELOS et al, 2010;RODRIGUES et al, 2011;ROSADO et al, 2012;). MULAMBA & MOCK (1978) have been the most adopted, certainly for its simplicity and positive results.…”
Section: Introductionmentioning
confidence: 99%